-2

Q ∧ S

(Q ∧ ¬P) → ¬R

Q → ¬P

(S ∧ T) → (P ∨ R)

The goal is:¬T

1

Derive a contradiction under the assumption of T, so that you may deduce ¬T by negation introduction.

|  Q ∧ S
|  (Q ∧ ¬P) → ¬R
|  Q → ¬P
|_ (S ∧ T) → (P ∨ R)
|  S                    ∧ E
|  Q                    ∧ E
:  :
|  |_ T
|  |  S ∧ T             ∧ I 
|  |  P ∨ R             → E
:  :  :
|  |  #
|  ¬T                   ¬ I
| improve this answer | |

Not the answer you're looking for? Browse other questions tagged or ask your own question.